2008
DOI: 10.1136/bmj.39408.481898.be
|View full text |Cite
|
Sign up to set email alerts
|

Community occupational therapy for older patients with dementia and their care givers: cost effectiveness study

Abstract: Objective To assess the cost effectiveness of community based occupational therapy compared with usual care in older patients with dementia and their care givers from a societal viewpoint.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
257
0
5

Year Published

2008
2008
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 242 publications
(266 citation statements)
references
References 25 publications
4
257
0
5
Order By: Relevance
“…[164][165][265][266][267][268][269] Grade B, Level 2 + B End-of-life care for patients with dementia has been found to be extremely demanding of family caregivers. The burden experienced can be personal, emotional and economic and can result in significant levels of depression in the caregivers.…”
Section: Needs Of Caregiversmentioning
confidence: 99%
“…[164][165][265][266][267][268][269] Grade B, Level 2 + B End-of-life care for patients with dementia has been found to be extremely demanding of family caregivers. The burden experienced can be personal, emotional and economic and can result in significant levels of depression in the caregivers.…”
Section: Needs Of Caregiversmentioning
confidence: 99%
“…5 After the recommendations from the consensus conference were finalized, the results of a single-blind randomized controlled trial of community-based occupational therapy for older patients with mild to moderate dementia and their primary caregiver were published. [6][7][8] The therapy comprised environmental modifications, compensatory strategies for the patient, and training of the caregiver to use effective supervision, problemsolving and coping strategies to sustain the autonomy and social participation of the patient and the caregiver. After 10 one-hour sessions over 5 weeks, statistically significant improvements were seen in the short term (3 months) in the daily functioning of patients in the intervention group.…”
Section: Nonpharmacologic Therapymentioning
confidence: 99%
“…In these trials, they have found occupational therapy to be cost-effective with adults with stroke or dementia, in reducing falls, and when provided as a preventive service (Godwin, Wasserman, & Ostwald, 2011;Graff et al, 2008;Hay et al, 2002;Steultjens, Dekker, Bouter, Jellema, et al, 2004). Most population-based research has focused on postacute care, hospital readmission, or geographic variation in outcomes related to inpatient rehabilitation services (Galloway et al, 2016;Reistetter et al, 2015).…”
mentioning
confidence: 99%